Troublemakers: Chicago freedom struggles through the lens of Art Shay - Gellman, Erik S. and Shay, Arthur (The University of Chicago Press, 2020)
Introduction -- Democratic dreams deferred -- Windy City justice -- Suburban civility -- Chicago's own civil rights movement -- Human rights and freedom marches -- Welcome democrats and black power -- Conclusion.
https://katalog.adlr.link/Record/0-1664464999